Kedudukan hukum dan hak waris anak hasil inseminasi buatan dari ayah yang telah meninggal - Cindy Olivia Susanto; Siti Hamidah Siti Hamidah; Rachmi Sulistyarini Rachmi Sulistyarini (University of Merdeka Malang, 2020)
This research aims to analyze Artificial Insemination Children’s Standing anddiscover Their Hereditary Right from a Deceased Father viewed in Indonesia’sPositive Law. Judgment will affect to whether artificial insemination from the deceasedhusband’s sperm can be performed or not. Further, the judgment that decidethe artificial insemination can be performed will affect children’s standing from adeceased father. If the children are born alive, then the standing is legal based on Article 250 of Civil Code, Islamic Law (Sharia law), and customary law. In addition,customary law claims the standing as adopt them on culture. Artificial inseminationchildren’s hereditary right from a deceased father has the right to inherit (asheir).How to cite item: Susanto, C., Siti Hamidah, S., Rachmi Sulistyarini, R. (2020). Kedudukan hukum dan hak waris anak hasil inseminasi buatan dari ayah yang telah meninggal. Jurnal Cakrawala Hukum, 11(3). 302-312.doi:10.26905/idjch.v11i3.5475.